2019
DOI: 10.3390/polym11050753
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Interfacial Strength of Carbon Fiber/Poly(ether ether ketone) Hybrid Composites by Plasma Treatments

Abstract: As a promising alternative to traditional prepreg, carbon fiber/poly(ether ether ketone) (CF/PEEK) hybrid composites have attracted wide public interest for their flexibility and conformability. However, modification methods focused on the hybrid premix have not been previously studied. In the present work, the interfacial strength of the hybrid composite was improved by treating the carbon and PEEK fibers together in a radiofrequency (RF) plasma containing one of the following gases to achieve surface activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Lu et al. [ 121 ] used a different plasma treatment than Brès et al. to improve the interfacial strength of carbon fiber/PEEK composites in a RF plasma by alternating 1 min of Ar atmosphere followed by 1 min of air atmosphere.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…Lu et al. [ 121 ] used a different plasma treatment than Brès et al. to improve the interfacial strength of carbon fiber/PEEK composites in a RF plasma by alternating 1 min of Ar atmosphere followed by 1 min of air atmosphere.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…The tensile stress concentrations in PAEK/CF composite lead to initial crack propagation in matrix material. 27 The fibre–matrix failure is observed as well making it an adhesive mode of failure.…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al demonstrated the enhancement of the interfacial strength of carbon fiber/poly(ether ether ketone) hybrid composites by plasma treatment [ 30 ]. Fiber-reinforced thermoplastic composites such as hybrid composites based on carbon fibers and poly(ether ether ketone) (CF/PEEK) are considered as viable options to replace conventional prepreg systems for applications across automotive, aerospace, and other industries.…”
Section: Plasma For Modifying Mechanical Properties Of Polymer Compositesmentioning
confidence: 99%
“…The energy for ionization is delivered into the chamber using a variety of means, with a radio frequency source of 13.56 MHz inductively coupled to the reactor being a common option ( Figure 1 b). In the example presented in Figure 1 c, the reactor operated at the power of 18 W and pressure of about 1 Torr, with gas supply to the reactor chamber at the rate of about 8 standard cubic centimeters per minute, producing excited plasma free radicals that are sufficiently energetic to cleave bonds present in organic molecules [ 30 ]. Radicals (i.e., molecular fragments, atoms, and ions) that are generated at the result of these bond breaks can engage in subsequent reactions with molecules in the gas and on the surfaces of the solid, producing volatile species.…”
Section: Introductionmentioning
confidence: 99%